(untitled) (Research, Society and Development, 2020)
Rainfall precipitation in Northeastern Brazil (NE) is characterized by high spatial and temporal variability. However, the availability of rainfall data is still limited in this region, for many reasons. Access to rainfall data could provide useful information to better understand rainfall distribution and support ecosystem management. In this paper, we present the program Guarda Chuvas, which makes viable access and visualization of historical rainfall data of the state of Pernambuco, NE Brazil, within a user-friendly environment. The trend surface analysis interpolation method was used to estimate values of monthly precipitation () for the state of Pernambuco on a grid with a resolution of 0.01 degree, totaling 81,544 monthly precipitation series spatially distributed over the state of Pernambuco. The program was developed in C language, with a graphical user interface developed using an application programming interface for Windows. The historical series provided by the program can be used as input for simulation models, and the program can support studies directed to the development of agricultural, water, environmental and socioeconomic policies for the state of Pernambuco. In addition to the regional interest in the data output from the program, the current approach should be found useful for applications in other parts of Brazil and the world.